2012
DOI: 10.4236/ajps.2012.32023
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling during Wilting in Chickpea Caused by <i>Fusarium oxysporum</i> F. sp. <i>Ciceri</i>

Abstract: <i>Fusarium oxysporum</i> f. sp. <i>ciceri</i> (<i>Foc</i>), one of the most important fungal pathogen of chickpea, is a constant threat to this crop plant. In the present study gene expression analysis of chickpea roots during <i>Foc</i> infection was performed using various approaches. cDNAs derived from total mRNA during infection process of susceptible (JG62)and resistant (Digvijay) cultivars, were amplified using random oligonucleotides. Sequence characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 39 publications
3
23
0
Order By: Relevance
“…() and Gurjar et al . () have reported that Bet v1 protein is responsible for resistance towards pathogen. Similarly, β‐1,3‐glucanase is involved in plant defence response against pathogen (Shetty et al ., ; Ward et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…() and Gurjar et al . () have reported that Bet v1 protein is responsible for resistance towards pathogen. Similarly, β‐1,3‐glucanase is involved in plant defence response against pathogen (Shetty et al ., ; Ward et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been carried out to identify the molecular basis of Foc resistance or susceptibility in chickpea using various approaches including gene mapping, candidate gene identification, differential expression and biochemical analysis postfungal infection (Ashraf et al ., ; Giri et al ., ; Gowda et al ., ; Gupta et al ., , ; Gurjar et al ., ; Nimbalkar et al ., ). However, genomic scale dynamics of plant–fungus interaction is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Plant-pathogen interaction is complex and involves the expression of both, pathogen virulence genes as well as plant defense genes. Till date, various candidate genes with prime role in fungal pathogenesis have been identified [ 7 ]. These fungal pathogenicity genes are categorized based on formation of infection structures, cell wall degradation, toxin biosynthesis, signaling and proteins suppressing plant defense [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The success of plant defense against pathogens depends on multiple events involved in the resistance. Moreover, these mechanisms of plant defense are governed by a range of genes singly or synergistically [ 23 ]. Some plants express resistance proteins that reveal the presence of specific elicitors, thereby leading to a strong defensive response, which is referred to as elicitor-triggered resistance [ 24 ].…”
Section: Introductionmentioning
confidence: 99%